Surgery Management Post Ovulatory Egg Stasis in Corn Snake (Pantherophis guttatus) - Sari, Dian Ayu Kartika; Apritya, Desty; Rahman, Muhammad Noor (Universitas Airlangga, 2022)
Post Ovulatory Egg Stasis or dystocia is difficulty releasing eggs. The incident was experienced by a female snake due to an obstructive tract. A four years old corn snake (Pantherophis guttatus) female with clinical symptoms that appear are anorexia for two weeks. The condition of the coelomic cavity is still large after 7 days of laying eggs. The results of physical examination showed that the snake had a distended coelomic cavity, pale mucous membrane, hard and smooth palpation when palpated. The results of x-ray examination showed that there was an oval radiopaque formation in the coelomic cavity. Coeliotomy surgery is performed to remove the eggs by the salpingotomy method. The general anesthetic used was a combination of zolazepam-tiletamine at a dose of 10 mg/kg body weight and meloxicam 0,1 mg/kg body weight was given. Postoperative therapy was oxytetracycline 10 mg/kg body weight, dexamethasone 5 mg/kg body weight and vigantol E® 0,1 mg/kg body weight. The general condition of the snake after 5 days improved and the wound had dried up. Then 2 weeks after surgery the stitches in the skin were removed when shedding of the skin.